Trends and Levels of Poaching in Wildlife Protected Areas of Ghana: A Case Study of the Kakum National Park - Frimpong, A. (University of Ghana, 2022)
Poaching has been an age-old challenge faced by park managers who are tasked to maintain and improve the ecological health of protected areas. Although poaching is a major challenge facing the Kakum National Park (KNP), a holistic research on how this menace has evolved since the gazette of the park 30 years ago is still lacking. This research therefore, was to investigate the key drivers of poaching as well as the law enforcement efforts and poaching trends of the KNP in the last 10 years (2011 to 2021). Data for the study was obtained from primary sources including key informant interviews with park staff and focus group discussions with 141 persons from 10 fringe communities. In addition to this secondary data from desktop reviews and quarterly reports of the park (2011 to 2021) were obtained to augment data needed. Analysis of data on poaching legislation was done through a comparative analysis of Ghana’s poaching laws and that of Nepal (the country with the least poaching in the world) to ascertain the effectiveness of Ghana’s laws. Socio-Ecological Systems (SES) framework was also adapted to analyze the drivers of poaching whereas semi-log linear regression was used to deduce the trends of poaching activities in the last 10 years. The model for catch per unit effort was used to measure law enforcement performance of the park (using Stata and MS Excel). The results show that laws used in prosecuting poaching cases are less punitive with very low fines and jail terms hence ineffective in controlling poaching. Economic hardship was identified as the main driver of poaching in the KNP. The trend analysis shows a significant reduction in the number of poachers arrested in the park suggesting that the poaching activities are gradually reducing which may be attributed to effective law enforcement or the poachers resorting to other ways of poaching without being noticed
MPhil.Biodiversity & Conservation Science
Keywords: Poaching; Kakum National Park (KNP); Ghana